Funcionamiento cognitivo, autonomía e independencia del adulto mayor institucionalizado (2018)
Introduction: Aging may cause deterioration of physical and mental capacities leading to dependency and disability and this situation is likely to be more frequent in the institutionalized older adult. Objective: To determine the cognitive functioning, the autonomy and independence of the institutionalized older adult. Methods: Cross-sectional, quantitative and descriptive study conducted in Sagrado Corazón de Jesús home for the elderly from September to November 2015. The universe of study was 62 institutionalized older adults and the final sample included 37 adults who met the inclusion criteria. The analysis instruments were Minimental State Examination, Assessment Scale of Autonomy for Self-care and the Autonomy Scale for the basic daily life activities-Barthel. Summary statistics was used to process information. Results: In the study, 51.20 % of participants were women, 48.80 % were men; 88.23 % aged 71 to 90 years; 32.40 % presented with severe cognitive deterioration; 24.20 % with moderate deterioration and 27 % was deterioration-free. As to the daily life activities, 76.70 % were completely autonomous; 5.10 % were dependent; 40.50 % were independent; 2.70 had slight dependence and 13.50 % showed severe or total dependency. Conclusions: The majority of older adults are autonomous and independent in doing their daily life activities, but cognitive functionality was the most deteriorated. © 2019 Revista Cubana de Enfermería.